Multimodal Semiotics in Cosmetic Advertisement - Ni Putu Meira Purnama Yanti; I Nyoman Sujaya; Mirsa Umiyati (RETORIKA: Jurnal Ilmu Bahasa, 2022)
This research deals with the elements of multimodal semiotics and the meaning of beauty. The theory used in this research was the multimodal semiotics theory by Kress and Leewuen (2011) in their book entitled Multimodal Discourse Analysis. The method applied in this research was a descriptive qualitative method. Based on data analysis, it was found that cosmetic advertisements have various multimodal semiotics such as verbal, visual, gestural, and audio. Verbal elements in the form of speech and writing which are dominated by declarative sentences. Visual elements refer to female figures in advertisements and other things with certain color. Gesture elements include smiling facial expressions, sparkling eyes, touching skin, and other movements. Audio elements come from bee sound effects, traditional Javanese music sounds, and so on. Meanwhile, the meanings of beauty conveyed through the multimodal semiotic elements refer to the meaning of physical beauty such as olive skin, white skin like jicama fruit, thick and beautiful hair, stormy hair, and graceful attitude.